Analysis of the Effectiveness of the Pakars Validation Application in Assessing Graduate Students’ Financial Eligibility and Awareness as a Strategy to Reduce Outstanding Receivables - Sinuraya, Amri; Umniati, Naeli (Journal La Sociale, 2025)
This study investigates the effectiveness of the Pakars Validation application in enhancing student eligibility identification and financial awareness as part of a strategic approach to reducing receivables in the Postgraduate Program at UQY University. The persistent problem of student receivables is often driven by the suboptimal utilization of flexible payment schemes and the limited dissemination of accurate information regarding students’ financial obligations. In response to these issues, the Pakars Validation application was developed to streamline administrative and financial validation processes, while automating email-based communications containing billing details and payment reminders. Employing a quantitative approach, the research utilized a survey method involving 100 active postgraduate students selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings indicate that the Pakars Validation application plays a significant mediating role between student eligibility identification and financial awareness with receivables reduction strategies. Direct effects of the independent variables on receivables reduction were not statistically significant, but became significant when mediated by the application. The study underscores the importance of integrated digital validation systems combined with technology-driven communication tools in improving receivables management. Practically, it recommends strengthening such applications as a core strategy to enhance financial stability and ensure the long-term sustainability of higher education institutions